Fundamental Particle and Forces - Sharma, Bhumi Raj (Himalayan Physics, 2017)
The study of particle physics is indispensable not only to understand different branch of science but also to unleash the most profound mysteries in natures such as the mystery of the origin of the Universe. Fundamental particles and their interactions in nature come under the study of Particle Physics, which studies the physical processes that occurs at scales even smaller than atomic nuclei. This article introduces elementary particles and forces, and then focuses on a few promising and interesting area of the particle physics. The Himalayan Physics Vol. 6 & 7, 2017 (123-125)